Սուրբ Գրիգոր Նարեկացի, Սուրբ Ներսէս Շնորհալի. հոգեւոր տաղերի այլաբանութիւնը - Ալվրցեան, Հայկազուն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматривается ряд вопросов, связанных с основным средством — духовным символом аллегорической речи в духовной поэзии великого армянского поэта средневековья Нерсеса Шнорали. Основной акцент сделан на принципах построения символического поэтического слова, восприятия духовного символа и раскрытии смыслов духовной аллегории. По определению Нерсеса Шнорали, главной предпосылкой понимания символического слова в средневековой духовной культуре является раскрытие невидимого, неосязаемого, абстрактного (скрытого, таинственного), известного немногим и только Богу, и сделать его ощутимым и ясным, поскольку видимая сторона творения (материальный мир — вторичный) является лишь средством его для познания невидимого мира (божественного, существенного) и достижения и общения с ней. The article discusses several questions related to the spiritual symbol — the main means of allegorical speech in the spiritual poem of the great medieval Armenian poet Nerses the Graceful. The main emphasis is on the construction of symbolic speech, the perception of the symbol and, in general, the disclosure of the meanings of spiritual allegory. According to Nerses the Graceful’s definition, the main prerequisite for understanding the symbolic speech in the medieval spiritual culture is to reveal the invisible, the intangible, the abstract (the hidden meaning) known to “the few and only God”, and make it comprehensible, because the visible side of the creation (the material world — the secondary one) is just a means for understanding its invisible side (the divine — the essential) and for being able to comprehend and communicate with it. The article examines a number of issues related to the main means of allegorical speech in the spiritual poem of the great medieval Armenian poet Nerses the Graceful.
Keywords: Հոգեւոր տաղեր